2022
DOI: 10.1016/j.fertnstert.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronavirus disease 2019 immunity on frozen-thawed embryo transfer cycles outcome

Abstract: Objective To study the effect of patients' immunization following COVID-19 infection or mRNA SARS-CoV-2 vaccine on frozen-thawed embryo transfer (FET). Design A cohort retrospective study Setting Tertiary University Affiliated Medical Center Patients All consecutive patients undergoing FET cycles in our center. The study group (immune- group) consisted of patients treated during the COVID-19 pandemic (between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 17 publications
6
57
1
5
Order By: Relevance
“…After the screening process, 39 articles were considered pertinent for potential inclusion and the full texts were retrieved. Finally, 29 articles [1] , [2] , [3] , [4] , [6] , [7] , [8] , [10] , [15] , [17] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Lifshitz et al, 2022; Mohr-Sasson et al, 2022; Morris, 2021; Morris et al, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Wesselink et al, 2022; Xia et al, 2022; Zhu et al, 2022)were included in the systematic review and 20 articles [2] , [3] , [4] , [6] , [7] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Morris, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Xia et al, 2022; Zhu et al, 2022) in the meta-analysis ( Figure 1 ).
Figure 1 Flowchart of the screening and selection process
…”
Section: Resultsmentioning
confidence: 99%
“…After the screening process, 39 articles were considered pertinent for potential inclusion and the full texts were retrieved. Finally, 29 articles [1] , [2] , [3] , [4] , [6] , [7] , [8] , [10] , [15] , [17] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Lifshitz et al, 2022; Mohr-Sasson et al, 2022; Morris, 2021; Morris et al, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Wesselink et al, 2022; Xia et al, 2022; Zhu et al, 2022)were included in the systematic review and 20 articles [2] , [3] , [4] , [6] , [7] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Morris, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Xia et al, 2022; Zhu et al, 2022) in the meta-analysis ( Figure 1 ).
Figure 1 Flowchart of the screening and selection process
…”
Section: Resultsmentioning
confidence: 99%
“…Several studies to date have also assessed the IVF pregnancy outcomes following COVID-19 vaccination, with no significant differences observed in biochemical, clinical or ongoing pregnancy rates [15][16][17][34][35][36]. By analyzing euploid blastocyst transfer cycles, our cohort offers a unique opportunity to investigate independently the possible detrimental effect of vaccine-induced autoimmunity on embryo implantation and pregnancy establishment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the history of SARS-CoV-2 infection was determined by patient self-report rather than seropositivity measurement. Therefore, the bias caused by withholding information from patients could also present a confounding risk since those unvaccinated but priorly infected patients should be deemed immunized as those vaccinated [42]. Secondly, our study was conducted in a single center with small sample size, especially in terms of pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported vaccine safety in women of reproductive age, with no adverse effects on fertility and reproductive function (Bentov et al, 2021;Hillson et al, 2021;Mohr-Sasson et al, 2022;Wainstock et al, 2021). Likewise, IVF outcomes such as implantation rates and clinical and ongoing pregnancy rates have not been negatively affected by vaccination (Aharon et al, 2022;Aizer et al, 2022;Orvieto et al, 2021). One recent study evaluating the effect of SARS-CoV-2 vaccination on IVF outcomes found number of oocytes retrieved and rate of good-quality embryos were comparable between vaccinated and unvaccinated groups (Huang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%